Daytime napping, sleep duration and serum C reactive protein: a population-based cohort study. Issue 11 (11th November 2014) - Leng, Yue; Ahmadi-Abhari, Sara; Wainwright, Nick W J; Cappuccio, Francesco P; Surtees, Paul G; Luben, Robert; Brayne, Carol; Khaw, Kay-Tee
Abstract : Objectives: To explore whether daytime napping and sleep duration are linked to serum C reactive protein (CRP), a pro-inflammatory marker, in an older aged British population. Design: Cross-sectional study. Setting: European Prospective Investigation into Cancer and Nutrition (EPIC)-Norfolk study. Participants: A total of 5018 men and women aged 48–92 years reported their sleep habits and had serum CRP levels measured. Outcome and measures: CRP was measured (mg/L) during 2006–2011 in fresh blood samples using high-sensitivity methods. Participants reported napping habits during 2002–2004, and reported sleep quantity during 2006–2007. Multivariable linear regression models were used to examine the association between napping and log-transformed CRP, and geometric mean CRP levels were calculated. Results: After adjustment for age and sex, those who reported napping had 10% higher CRP levels compared with those not napping. The association was attenuated but remained borderline significant (β=0.05 (95% CI 0.00 to 0.10)) after further adjustment for social class, education, marital status, body mass index, physical activity, smoking, alcohol intake, self-reported health, pre-existing diseases, systolic blood pressure, hypnotic drug use, depression and in women-only hormone replacement therapy use. The geometric means (95% CI) of CRP levels were 2.38 (2.29 to 2.47) mg/L and 2.26 (2.21 to 2.32) mg/L for those who reported napping and no napping, respectively. A U-shaped association was observed between time spent in bed at night and CRP levels, and nighttime sleep duration was not associated with serum CRP levels. The association between napping and CRP was stronger for older participants, and among extremes of time spent in bed at night. Conclusions: Daytime napping was associated with increased CRP levels in an older aged British population. Further studies are needed to determine whether daytime napping is a cause for systemic inflammation, or if it is a symptom or consequence of underlying health problems.